The Job Satisfaction Mediation Dilemma: A Case Study of Work Engagement and Organizational Culture’s Influence on Employee Performance at the Regional Development Planning, Research, and Development Agency of Fakfak Regency - Bere, Titus Agusto; Subyantoro, Arief; Nilmawati, Nilmawati (CV. Strata Persada Academia, 2025)
This study investigates the direct and indirect effects of work engagement and organizational culture on employee performance, with job satisfaction examined as a mediating variable, in the context of the Regional Development Planning, Research, and Development Agency of Fakfak Regency, Indonesia. Employing a quantitative research design and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from a saturated sample of 54 civil servants using validated survey instruments. The findings reveal that both work engagement and organizational culture have significant direct impacts on employee performance. However, job satisfaction does not significantly mediate these relationships, challenging prevailing assumptions in public sector performance theory. These results imply that enhancing employee performance in government institutions may be more effectively achieved through direct investments in engagement and organizational culture rather than relying solely on job satisfaction as a psychological intermediary. The study offers empirical contributions to public management literature and provides practical recommendations for local government agencies aiming to improve workforce productivity and strategic planning outcomes. Future research should explore alternative mediators or moderators and utilize longitudinal approaches to better capture the complexity of organizational dynamics.